Impact of COVID-19 lockdown on lifestyle adherence in stay-at-home patients with chronic coronary syndromes: Towards a time bomb. (15th January 2021) - Cransac-Miet, Amélie; Zeller, Marianne; Chagué, Frédéric; Faure, Agnès Soudry; Bichat, Florence; Danchin, Nicolas; Boulin, Mathieu; Cottin, Yves
Abstract: Background: We aimed to evaluate the impact of coronavirus disease 2019 (COVID-19)-related lockdown on adherence to lifestyle and drug regimens in stay-at-home chronic coronary syndromes patients living in urban and rural areas. Methods: A cross-sectional population-based study was perfomed in patients with chronic coronary syndromes. A sample of 205 patients was randomly drawn from the RICO (Observatoire des infarctus de Côte d'Or) cohort. Eight trained interviewers collected data by phone interview during week 16 (April 13 to April 19), i.e. 4 weeks after implementation of the French lockdown (start March 17, 2020). Results: Among the 195 patients interviewed (of the 205, 3 had died, 1 declined, 6 lost), mean age was 65.5 ± 11.1 years. Only six patients (3%) reported drug discontinuation, mainly driven by media influence or family members. All 166 (85%) patients taking aspirin continued their prescribed daily intake. Lifestyle rules were less respected since almost half (45%) declared >25% reduction in physical activity, 26% of smokers increased their tobacco consumption by >25%, and 24% of patients increased their body weight > 2 kg. The decrease in physical activity and the increase in smoking were significantly greater in urban patients (P  < .05). Conclusions: The COVID-19-related lockdown had a negative impact on lifestyle in a representative sample of stay-at-home CCS patients. Highlights: Consequences of COVID-19 lockdown in stay-at-home chronic coronary syndromes patients is unknown. Patients reported a very high cardiovascular drug adherence. Lockdown negatively impacted lifestyle management.